Studi Kasus : Kesembuhan Kasus Feline Panleukopenia pada Kucing Mocca di Surabaya - Intan Permatasari Hermawan; Geta Darantika; Rikar Antonio Tage; Kurnia Desiandura; Hana Cipka Pramuda Wardhani (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
Feline panleukopenia is an infectious disease caused by a virus from the Parvoviridae family. This virus can infect cats of all ages with high morbidity and mortality rates. Mocca cat, male, 5 years old, weighs 3 kg with simptoms are 3 days of diarrhea, does not want to eat for 1 day, always salivates, has not been vaccinated, has not been given worm medicine, had bloody diarrhea, and a cat often let loose. The results of the physical examination showed the cat was dehydrated, stomatitis, otitis, weakness, hypersalivation, bloody diarrhea, and body temperature reached 39.9 °C. Diagnose to this case using the Ag-FPV test kit that showed positive. Hematological examination showed decreasing in RBC, HGB, HCT, MCV, MCH and MCHC as well as an increase in leukocytes, granulocytes, monocytes and lymphocytes. The therapy given infusion of 0.9% NS fluids, injection of trimethoprim & sulfadoxine, tolfenamic acid and multivitamins, as well as oral drugs in the form of methylprednisolone, vitamins and transfer factors. After 5 days of therapy, Mocca's cat was declared cured